The complete mitochondrial DNA for the Fujian Bamboo-leaf Frog Odorrana exiliversabilis (Anura: Ranidae) by next-generation sequencing. Issue 2 (1st February 2021) - Zhong, Jun-Jie; Ma, Li; Lin, Zhi-Hua; Ding, Guo-Hua; Luo, Si-Te
Abstract: The complete mitochondrial DNA (mtDNA) for Odorrana exiliversabilis Li, Ye and Fei 2001 (Anura: Ranidae) was determined in this study. The length of complete mtDNA was 17, 122 bp, including 13 PCGs (COI-III, ND1-6, ND4L, ATP6, ATP8 and CYTB), 25 tRNA genes, 2 rRNA genes, 2 non-coding regions of a L-strand replication origin and a control region. The overall base composition of the sequence is 28.27% T, 28.27% C, 28.52% A, and 14.94% G, with a total A + T content of 56.79%. The phylogenetic tree showed that O. exiliversabilis was the sister species of O. tormota, and formed a monophyletic clade with other Odorrana species. These data provide a powerful tool for evolutionary biology and population genetics of genus Odorrana .